2018
DOI: 10.1007/s00415-018-8816-9
|View full text |Cite|
|
Sign up to set email alerts
|

Caregiver burden and its related factors in advanced Parkinson’s disease: data from the PREDICT study

Abstract: IntroductionCaring for a person with Parkinson’s disease (PD) is associated with an increased risk of psychiatric morbidity and persistent distress. The objective of this study was to describe the burden and the related factors of caregivers of advanced PD (APD) patients either treated with continuous dopaminergic delivery systems or standard therapy.MethodsThis cross-sectional, epidemiologic study conducted in 13 Italian sites enrolled PD patients treated with continuous dopaminergic delivering systems [eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 26 publications
(37 reference statements)
2
62
0
2
Order By: Relevance
“…71 Therefore, other approaches, such as nonpharmacologic therapies, should be investigated. However, the patient's functioning is also dependent on how partners or caregivers cope with the disease of their loved one and the extent to which this influences their own lives.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…71 Therefore, other approaches, such as nonpharmacologic therapies, should be investigated. However, the patient's functioning is also dependent on how partners or caregivers cope with the disease of their loved one and the extent to which this influences their own lives.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Some studies focusing on this issue have been published, but we considered caregiver outcomes to be beyond the scope of this review. 71,72 4.3 | Implications for research, policy, and practice Our review identified several correlates of impaired social role performance in PD, including disease severity, anxiety, depression, and cognitive impairment. However, less attention has been paid to interventions or methods of preserving or improving social role functioning.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Mindfulness could help to improve coping and reduce stress of the caregivers. In PD, the caregiving situation becomes increasingly stressful with disease progression [4,44,47,50,52] and mindfulness might be particularly helpful during later stages of the disease. Additionally, mindfulness may help to mitigate caregivers' tendency to overcommit in the caregiver role [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Caregiving involves significant time contributions, emotional commitment, and physical labor-and reduced involvement or relinquishing of previously valued roles-on the part of the person providing care, all of which may lead to adverse and compromised health and wellbeing outcomes (Carretero et al 2009). While this concept of burden has been extremely influential (Burke et al 2018;Tessitore et al 2018), highlighting the importance of carer wellbeing, it has simultaneously led people to think about caring in negative terms precisely because it constructs the care relationship as unidirectional, in which the independence and autonomy of the carer is compromised by the care needs of the dependent care-recipient.…”
Section: Care and Burdenmentioning
confidence: 99%